Sensory perception and its representations in the artistic productions of art education students (Journal of the College of Basic Education, 2025)
Sensory perception is one of the most important topics that has received the attention of psychologists and researchers in this field because of its importance in the life of the individual, as the process of sensory perception is a complex process in which the process of learning, perception and memory overlap. The aim of the research is to: - Build a tool to measure sensory perception among art education students - Reveal the representations of sensory perception in the artistic products of art education students, for the academic years (2019-2023), The theoretical framework included the concept of sensory perception, and artistic products (sensory perception and its relationship to the mediator of artistic production) and the chapter concluded with indicators and a presentation of previous studies, A random sample of (5) artistic paintings was selected, according to an analysis tool, with the presentation of conclusions and recommendations based on the results.